DOI: 10.11606/d.22.2003.tde-18052004-102251
|View full text |Cite
|
Sign up to set email alerts
|

"As crianças e os adolescentes acidentados no trabalho e atendidos em uma unidade distrital de saúde em Ribeirão Preto (SP)"

Abstract: Se um dia já homem feito e realizado sentires que a terra cede a teus pés, que tuas obras desmoronaram, que não há ninguém a tua volta para estender a mão, esqueça a tua maturidade, passe pela tua mocidade, volte a tua infância e balbucie entre lágrimas e esperança as últimas palavras que sempre te restarão na alma: minha mãe, meu pai. Rui Barbosa DEDICATÓRIA Aos meus irmãos, Ronan e Ronaldo, que sempre estiveram dispostos a me ajudar e, acima de tudo, a me proteger nos momentos difíceis. Ao meu sobrinho, Davi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
7

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 4 publications
0
3
0
7
Order By: Relevance
“…they happened at the workplace or on the way to the workplace (23.1%), and this information coincides with other investigations. [7][8][9][18][19] More than half of these accidents (61.5%) happened during the afternoon and the most affected body parts were the legs and feet (46.2%); in relation to the types of injuries, four (30.8%) reported abrasions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…they happened at the workplace or on the way to the workplace (23.1%), and this information coincides with other investigations. [7][8][9][18][19] More than half of these accidents (61.5%) happened during the afternoon and the most affected body parts were the legs and feet (46.2%); in relation to the types of injuries, four (30.8%) reported abrasions.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the accidents (60.7%) were typical and 51.8% of the participants had their upper limbs injured as a result of cutting objects. 19 A research undertaken in the city of Ipatinga-MG in 2008, which investigated the occurrence of OAs involving teenagers, concluded that 42% of these workers claimed to have been victims of accidents at the workplace and 14.9% had to stay away from work for this reason. More than half (51.4%) were not legally registered; cuts and punctures were the most common injuries (27.5%); burn was the main injury (26.9%); and the most affected body parts were the legs and fingers (40.4%).…”
Section: Resultsmentioning
confidence: 99%
“…As for gender, 72.6% were women, a reality that differs from evidence in other studies (5)(6)(7)17) , appointing that men are included in the job market earlier. It is known that the number of young working girls is frequently underestimated in statistical data, which generally do not take into account nonremunerated work in and outside the family group (18) . Two adolescents mentioned they had a child (1.7%).…”
Section: Discussionmentioning
confidence: 99%
“…A Unidade Básica de Saúde (UBS) constitui a porta de entrada no sistema, executando o atendimento e encaminhamentos necessários para outros serviços e especialistas. O acolhimento e atendimento das urgências de baixa gravidade ou complexidade são atribuições e prerrogativas das UBS que devem ser desempenhadas por todos os municípios brasileiros (3) .…”
Section: Introductionunclassified